Ordered three-fold symmetric graphene oxide/buckled graphene/graphene heterostructures on MgO(111) by carbon molecular beam epitaxy. Issue 15 (3rd April 2018) - Ladewig, Chad; Cheng, Tao; Randle, Michael D.; Bird, Jonathan; Olanipekun, Opeyemi; Dowben, Peter A.; Kelber, Jeffry; Goddard, William A.
Abstract : Theory and experiment demonstrate the direct growth of a graphene oxide/buckled graphene/graphene heterostructure on an incommensurate MgO(111) substrate. Abstract : Theory and experiment demonstrate the direct growth of a graphene oxide/buckled graphene/graphene heterostructure on an incommensurate MgO(111) substrate. X-ray photoelectron spectroscopy, electron energy loss, Auger electron spectroscopy, low energy electron diffraction, Raman spectroscopy and first-principles density functional theory (DFT) calculations all demonstrate that carbon molecular beam epitaxy on either a hydroxylated MgO(111) single crystal or a heavily twinned thin film surface at 850 K yields an initial C layer of highly ordered graphene oxide with C 3v symmetry. A 5 × 5 unit cell of carbon, with one missing atom, forms on a 4 × 4 unit cell of MgO, with the three C atoms surrounding the C vacancy surface forming covalent C–O bonds to substrate oxide sites. This leads to a bowed graphene-oxide with slightly modified D and G Raman lines and a calculated band gap of 0.36 eV. Continued C growth results in the second layer of graphene that is stacked AB with respect to the first layer and buckled conformably with the first layer while maintaining C 3v symmetry, lattice spacing and azimuthal orientation with the first layer. Carbon growth beyond the second layer yields graphene in azimuthal registry with the first two C layers, but with graphene-characteristic lattice spacing and π → π* loss feature. This 3rd layer is also p-type, as indicated by the 5.6 eV energy loss feature. The significant sp 3 character and C 3v symmetry of such heterostructures suggest that spin–orbit coupling is enabled, with implications for spintronics and other device applications.